Designing Decentralized Ledger Technology for Electronic Health Records - Dhillon, Vikram (Telehealth and Medicine Today, 2018)
No abstract available. Editor’s note: A proposal to implement distributed ledger technology for electronic health records is outlined here. The rationale for integration of distributed ledgers in the healthcare domain is introduced, followed by a discussion of the features enabled by the use of a blockchain. An open source implementation of a distributed ledger is then presented. The article concludes with an examination of opportunities and challenges ahead in deploying blockchains for digital health.